Climate Change and Rural Women’s Participation in Rice Processing: Challenges and Prospects in Wushishi, Niger State, Nigeria - Dauda, Nma; Eze, J. N; Isaac, Y; Yunusa, B. J; Usman, B; Opaluwa, D.; Emmanuel, A. J. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
Climate change poses significant threats to rural women’s livelihoods in Niger State’s Wushishi Local Government Area, where rice processing is a vital economic activity. This study examined the percentage of rural females involved in rice processing in the area, with a focus on their socioeconomic characteristics, participation levels, and challenges faced. A multistage random sampling technique was used to select 125 processors from five processing towns in the Wushishi local government area. The data was analyzed using Net Farm Income and descriptive statistics. The results indicate that 67.2% of the processors were between the ages of 30 and 50. However, climate change affects their participation in rice production, as they face increased labor burdens, reduced access to resources, and limited decision-making power. The study found that 78.4%, 64.0%, and 56.0% of participants declined to take part in the rice harvesting, threshing, and winnowing processes, respectively. In contrast, 66.4%, 96.0%, 93.6%, and 87.2% of the processors engaged in grinding, drying, parboiling, and storage. Each respondent’s net farm income was ₦24,697.37, indicating the profit from rice processing in the Wushishi area. The primary obstacles faced by the participants included insufficient credit facilities, insufficient money, substandard storage facilities, unreliable transit routes, unstable electrical supplies, and lack of technical processing expertise, all of which are exacerbated by climate change. Policy considerations should prioritize making incentives available for upgrading processing technologies that will increase the rice processing process and provide better products with high market value and gain, thereby enhancing the resilience of rural women in the face of climate change. Additionally, respondents should establish cooperatives to strengthen their position in rice processing and advocate for improved access to credits, farm inputs, and climate-resilient agricultural practices.